What is behind native-immigrant social income gaps? - Lubomira Anastossova; Teodora Paligorova (Luxembourg Income Study (LIS), 2006)
The recent EU expansion raised fears of potential migration motivated by welfare receipt. In this paper we use comparable data from five countries - Sweden, Belgium, Germany, Norway and the U.S. - to ask whether immigrants benefit more from social support than natives. Looking at the European countries, we distinguish between migrants within and from outside the EU and find that within - EU migrants are similar to natives both in terms of their characteristics and social support receipt. On the other hand, we confirm the existence of large social income gaps in favor of non - EU immigrants, but these gaps are mainly due to the fact that immigrants' families have more children, fewer earners and are more likely to have no wage income. Household characteristics play a key role in 'explaining' the gap in Scandinavian countries, while individual characteristics are equally important in Belgium. In contrast to the European situation, U.S. immigrants receive less social income than natives and this is attributable mainly to their different individual characteristics.
Keywords: J6; J61; 330; Immigration; European Union; Social Benefits; Einkommensverteilung; Öffentliche Sozialleistungen; EU-Staaten; USA; Schweden; Belgien; Deutschland; Norwegen; Migranten